RDW – nowy marker dla chorób sercowo-naczyniowych = RDW - a new marker for cardiovascular disease - Surowiec, Agnieszka; Wołowiec, Łukasz; Rogowicz, Daniel; Kałużny, Krystian; Surowiec, Justyna; Tarczykowska, Agata; Krakowska, Alicja; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Surowiec Agnieszka, Wołowiec Łukasz, Rogowicz Daniel, Kałużny Krystian, Surowiec Justyna, Tarczykowska Agata, Krakowska Alicja, Zukow Walery. RDW – nowy marker dla chorób sercowo-naczyniowych = RDW - a new marker for cardiovascular disease. Journal of Education, Health and Sport. 2015;5(7):453-460. ISSN 2391-8306. DOI 10.5281/zenodo.20975 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A453-460 https://pbn.nauka.gov.pl/works/590771 http://dx.doi.org/10.5281/zenodo.20975 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 15.07.2015. RDW – nowy marker dla chorób sercowo-naczyniowych RDW - a new marker for cardiovascular disease Agnieszka Surowiec1, Łukasz Wołowiec1, Daniel Rogowicz1, Krystian Kałużny2, Justyna Surowiec3, Agata Tarczykowska4, Alicja Krakowska2, Walery Zukow5 1Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 2Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu; 3Studenckie Koło Naukowe Anatomii Topograficznej Człowieka, Katedra Anatomii Człowieka, Międzynarodowy Uniwersytet Medyczny w Ivano- Frankivsku; 4Studenckie Koło Naukowe Biomed, Wydział Inżynierii Mechanicznej, Uniwersytet Technologiczno-Przyrodniczy, Bydgoszcz; 5Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy; Słowa kluczowe: RDW, marker, choroby sercowo-naczyniowe. Key words: RDW, marker, cardiovascular diseases. Streszczenie Rozpiętość rozkładu objętości erytrocytów (red cell distribution width - RDW) jest wskaźnikiem zmienności wielkości krwinek czerwonych (anizocytoza). Krwinki czerwone zazwyczaj mają standardową wielkość, ale zaburzenia prowadzące do nieskutecznego procesu erytropoezy lub sytuacje zwiększonego niszczenia krwinek czerwonych doprowadzają do większej różnorodności w wielkości krwinki czerwonej, co przekłada się na wzrost wskaźnika RDW. RDW jest parametrem rutynowo oznaczanym w praktyce klinicznej jako część morfologii krwi, jest obecnie stosowany jako pomoc w diagnostyce różnicowej anemii. W celu poprawy stratyfikacji ryzyka chorób sercowo-naczyniowych identyfikacja nowych markerów prognostycznych może zapewnić poznanie dokładnej patofizjologii tych chorób oraz dać nowe możliwości terapeutyczne. Aktualnie szereg różnych parametrów i markerów biologicznych jest wykorzystywana do tworzenia modeli w celu przewidywania przeżycia pacjenta z daną chorobą sercowo-naczyniową. Najnowsze dane sugerują również, że RDW może być istotnym prognostycznie markerem dla śmiertelności długoterminowej w szeregu chorób układu sercowo-naczyniowego, w tym choroby wieńcowej, zawału mięśnia sercowego, niewydolności serca, udaru mózgu, nadciśnienia płucnego i choroby tętnic obwodowych. Abstract Red cell distribution width (RDW) is an index of the variation in red cells size (anisocytosis). Usually, red blood cells have a standard size, but disorders leading to ineffective erythropoiesis or situations of increased red blood cell destruction cause greater heterogeneity in red blood cell size, with a higher RDW value. Red cell distribution width is routinely measured in clinical practice as part of the automated complete blood count. Red cell distribution width is currently used as a diagnostic aid in the differential diagnosis of anemia because it reflects variability in the size of circulating erythrocytes. Higher values reflect greater heterogeneity in erythrocyte cell sizes. To improving risk stratification, identification of new prognostic markers may provide insight into underlying pathophysiology or suggest avenues for therapeutic development. To date, a wide variety of clinical variables and biological markers have been used to create predictive models for survival in patients with cardiovascular disease. Recent data also suggest that red cell distribution width also may be a prognostic marker for long-term mortality. This has been particularly well studied in patients with cardiovascular disease, including coronary disease, myocardial infarction, heart failure, strokes, pulmonary hypertension and peripheral artery disease.